2014
DOI: 10.1002/ajhb.22536
|View full text |Cite
|
Sign up to set email alerts
|

Association of television viewing time with central obesity status in rural Asian Indian Women: Santiniketan women study

Abstract: Increased leisure-time activity was associated with central obesity status and warrant early intervention to prevent increasing incidences of cardiovascular disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Watching TV, another sedentary behaviors, was positively associated with high triglyceride and high glucose, (ORs of 2.59 and 13.9 respectively for watching TV ≥ 21h/week vs. 0–5 h/week) in Taiwanese adults [ 10 ] and associated with central obesity in rural Indian women [ 50 ]. We found that watching TV over 14h/w was associated with a risk of high waist circumference in men (OR = 1.20) and high triglyceride in women (OR = 1.09), compared with people watching TV 7 hours per week or less.…”
Section: Discussionmentioning
confidence: 99%
“…Watching TV, another sedentary behaviors, was positively associated with high triglyceride and high glucose, (ORs of 2.59 and 13.9 respectively for watching TV ≥ 21h/week vs. 0–5 h/week) in Taiwanese adults [ 10 ] and associated with central obesity in rural Indian women [ 50 ]. We found that watching TV over 14h/w was associated with a risk of high waist circumference in men (OR = 1.20) and high triglyceride in women (OR = 1.09), compared with people watching TV 7 hours per week or less.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies with objective measures of sedentary time that include television viewing time have reported associations of total sedentary time with body composition, obesity, and adiposity. [17,4144] It has been shown that obesity is associated with reduced disc height [45] and increased fat mass is associated with LBP. [34,46] In this study, however, we have adjusted for BMI.…”
Section: Discussionmentioning
confidence: 99%